Life cycle greenhouse gas emissions of electricity generation from corn cobs in Ontario, Canada. (9th April 2014) - Sanscartier, David; Dias, Goretty; Deen, Bill; Dadfar, Humaira; McDonald, Ian; MacLean, Heather L.
Abstract: Policy initiatives have motivated a search for environmentally sustainable alternatives to fossil‐fuel‐based electricity generation. Agricultural residues such as corn cobs may be a suitable feedstock. A life cycle approach was used to estimate the greenhouse gas (GHG) emission impacts associated with the use of pellets produced from corn cobs as the sole fuel for the generation of electricity at a hypothetically retrofitted coal‐fired generating station in Ontario, Canada. Pellets are compared with current coal and hypothetical natural gas combined cycle (NGCC) facilities. A life cycle model and soil carbon model calibrated for the agricultural region of interest were combined to quantify the GHG emissions of the biomass product system. The corn cob product system's life cycle emissions (240 g CO2 eq kWh −1 ) are 40% and 80% lower than those of the NGCC and coal product systems, respectively. If corn cobs are left in the field to decompose, some carbon is sequestered in the soil, thus their removal from the field and combustion at the generation station represents a net GHG emission, accounting for 60% of life cycle emissions. In addition to the GHG impacts of combustion, removing agricultural residues from fields may reduce soil health, increase erosion and affect soil fertility through loss of soil organic carbon and nutrients. Their sustainable use should therefore consider the maintenance of soil fertility over the long‐term. Nevertheless, the use of the feedstock in place of coal may provide substantial GHG emissions mitigation.